Cocrystallization of 5-fluorouracil and l-phenylalanine: the first zwitterionic cocrystal of 5-fluorouracil with amino acid exhibiting perfect in vitro/vivo pharmaceutical properties. Issue 30 (15th July 2020) - Wang, Lin-Lin; Wang, Ling-Yang; Yu, Yue-Ming; Li, Yan-Tuan; Wu, Zhi-Yong; Yan, Cui-Wei
Abstract : The first zwitterionic cocrystal of 5-fluorouracil with amino acid has been prepared and its structure and in vitro / vivo properties have been systematically studied. Abstract : In order to highlight the advantages of l -phenylalanine (Phe) in the optimization of the in vitro / vivo properties of the anticancer drug 5-fluorouracil (Fu) along with the enhancement in its antitumor activities, the first zwitterionic cocrystal of Fu with the amino acid, abbreviated as Fu–Phe, has been successfully synthesized via a pharmaceutical cocrystallization technique. The exact structure of Fu–Phe has been determined by single-crystal X-ray diffraction analysis, which confirms that the cocrystal lattice consists of Fu and Phe molecules in equal ratio, and a variety of hydrogen bonds, especially the charge-assisted hydrogen bonds introduced by zwitterionic Phe, support the three-dimensional supramolecular network. The in vitro and in vivo properties of the newly synthesized cocrystal have been systematically evaluated. It can be concluded that both the permeability and dissolvability of Fu from the cocrystal are enhanced with respect to free Fu, and the degree of increase in the former is comparatively more obvious than that in the latter. It is worth mentioning that the ameliorated in vitro biopharmaceutical property of Fu together with the potential carrier role of Phe can not only significantly enhance the antitumor activity of Fu, thus displaying better time-dependent cytotoxicity against the tested tumor cell lines, but can also effectively enhance into the in vivo pharmacokinetic performance, thus showing accelerated peak plasma concentration and prolonged half-life as well as increased bio-availability in contrast to pure Fu. The present contribution provides a new solid crystalline form of Fu with a broad application prospect and a potential commercial value, thus leading to the research and development of zwitterionic amino acid antitumor cocrystal drugs based on cocrystallization strategy.